Thermomechanical Wear Testing of Metal Matrix Composite Cladding for Potential Application in Hot Rolling Mills. Issue 5 (5th May 2020) - Domitner, Josef; Aigner, Michael; Stern, Thomas; Paar, Armin; Sommitsch, Christof; Elizondo, Leonel
Abstract : The cover shows the microstructure of a metal matrix composite consisting of tungsten carbide particles embedded in a nickel alloy matrix. The diameter of the spherical particle at the center is about 40 μm. The EDX maps illustrate different contents of tungsten (orange) and nickel (yellow) inside the particles and inside the matrix, respectively. Further information can be found in the article by Josef Domitner and co‐workers, article number 1900478 .